Acupuncture as an independent or adjuvant therapy to standard management for menopausal insomnia: A systematic review and meta-analysis - Zhang, Xiaoni; Liu, Chengyong; Qin, Shan; Chen, Chaoming; Wang, Xiaoqiu; Jiang, Yuanyuan; Wu, Wenzhong (PloS one, 2025)
This systematic review aimed to clarify if acupuncture is more effective for menopausal insomnia compared with sham acupuncture, standard care (sedative hypnotics and/or MHT) or waitlist control. Seven literature databases were searched on April 30, 2024, to identify RCTs assessing the effectiveness of acupuncture. The methodological quality was assessed by the Cochrane Collaboration, and meta-analyses were conducted to calculate comparative effects using Rev Man software. 28 RCTs were analyzed. Six sham acupuncture-controlled RCTs were notable because of their high quality, and they showed that acupuncture significantly lowered PSQI scores, increased TST, sleep efficiency, and reduced WASO. The effect of acupuncture was maintained at a 4-week follow-up. Sixteen RCTs compared acupuncture with standard care, which showed acupuncture significantly reduced PSQI scores, KI scores, HAMD and HAMA scores. However, the subgroup analysis showed that there was no obviously difference between acupuncture and western medication in the treatment duration >8 weeks. Five RCTs assessed acupuncture combined with standard care and showed a favorable reduction in the PSQI score than standard care. One RCT showed that acupuncture significantly reduced PSQI and KI scores than a waitlist control. The GRADE assessment demonstrated that the level of evidence was very low to moderate, probably for the poor methodological quality and substantial heterogeneity among studies. The results showed that acupuncture may play a positive role in patients with menopausal insomnia.